Non-lesional focal epilepsies: epileptogenic zone diagnosis using deep electrodes in a high complex public hospital - Nasimbera, Alejandro (2019)
Purpose : Epilepsy surgery is the most effective method in the treatment of focal epilepsies when the epileptogenic zone (EZ) coincides with lesion in the MRI and does not involve eloquent areas. In those cases where EZ is not identified by neuroimaging methods, the implantation of deep electrodes is required for the adequate diagnosis of EZ. The aim of this study is to perform a descriptive analysis of the EZ diagnoses and the post- surgical evolution compared with the group of patients (p) with lesion in the MRI. Method : We analyzed the totality of patients implanted with deep electrodes (SEEG), from the Video- EEG Unit of El Cruce Hospital “Nestor Carlos Kirchner”, from January 2014 to December 2018, and selected those p without MRI lesion. We compared post surgical evolution of this selected group with the those p with MRI lesion. Results : From 30 p with deep electrodes (SEEG), 7 p (23%) had no lesion in the MRI. Four p. were implanted with deep electrodes in both mesial temporal regions. Two p, was bilateral temporal and prefrontal deep electrodes. The remaining p was explored in the posterior temporal region and right parietal. In 5 p surgery was indicated and 1 p remained seizure free. In 4 p we observed improve on seizures frequency. Compared with the population with a lesion in the MRI that was operated (12p), 4 p remain seizure free, 6 continued with lower seizure frequency and 2 p with sporadic seizures (p < .05). Conclusion : Post surgical evolution compared with the group of patients with lesion in the MRI, did not present significant differences. In the group of patients with focal drug resistant epilepsy without lesion in MRI, it is essential to perform SEEG with a multidisciplinary approach for a correct diagnosis of EZ and adequate response to surgical treatment.